2018
DOI: 10.1017/s0950268818001486
|View full text |Cite
|
Sign up to set email alerts
|

Severe morbidity among hospitalised adults with acute influenza and other respiratory infections: 2014–2015 and 2015–2016

Abstract: Our objective was to identify predictors of severe acute respiratory infection in hospitalised patients and understand the impact of vaccination and neuraminidase inhibitor administration on severe influenza. We analysed data from a study evaluating influenza vaccine effectiveness in two Michigan hospitals during the 2014-2015 and 2015-2016 influenza seasons. Adults admitted to the hospital with an acute respiratory infection were eligible. Through patient interview and medical record review, we evaluated pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Our results are similar to those reported by Lavery et al, however they reported on same-hospital re-admission 5 . These rates are also similar to those reported for patients hospitalized with acute respiratory illness secondary to seasonal influenza virus, patients hospitalized with community acquired pneumonia, or patients hospitalized in medical and geriatric wards 21 , 24 27 . They are lower than reported for patients hospitalized because of exacerbation of chronic pulmonary disease or congestive heart failure 25 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are similar to those reported by Lavery et al, however they reported on same-hospital re-admission 5 . These rates are also similar to those reported for patients hospitalized with acute respiratory illness secondary to seasonal influenza virus, patients hospitalized with community acquired pneumonia, or patients hospitalized in medical and geriatric wards 21 , 24 27 . They are lower than reported for patients hospitalized because of exacerbation of chronic pulmonary disease or congestive heart failure 25 .…”
Section: Discussionsupporting
confidence: 82%
“…Hypertension and malignancy were also more common in re-admitted non-severe patients with COVID-19 12 . These variables were also described as risk factors for re-admission among medical and geriatric patients, patients with seasonal influenza of community acquired pneumonia 20 , 21 , 24 , 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a slightly larger proportion of patients with Influenza have underlying comorbidities such as hypertension, diabetes, or COPD. In previous studies, these factors have been associated with a complicated course of Influenza infection ( Lina et al, 2020 , Schanzer et al, 2008 , Segaloff et al, 2018 ). In accordance, the reported comorbidities are similarly frequent in patients with COVID-19 with severe disease progression, increase with advanced age, and might be associated with a poor outcome ( Aggarwal et al, 2020 , Brück, 2020 , Richardson et al, 2020 , Zhou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…Considering the high number of participants required to power vaccine efficacy trials that are based on LCII and LCII-related outcomes, many have argued that accurate immunological correlates of protection should be given consideration as an alternative primary outcome, at least in the early phases of vaccine development [ 7 ]. This approach is especially practical for important subgroups of the population, such as older adults living with frailty and/or chronic conditions, who are at an increased risk of influenza hospitalization [ 8 ] and severity of related outcomes [ 9 ], regardless of vaccination status [ 10 ]. That being said, few correlates have been validated in older adults, and those that have are based primarily on hemagglutination inhibition antibody responses [ 11 , 12 ], which do not provide appreciable cross-strain immunity within the subtypes of influenza.…”
Section: Introductionmentioning
confidence: 99%